Benzodiazepines: A Major Component in Unintentional Prescription Drug Overdoses With Opioid Analgesics. (February 2014) - Jann, Michael; Kennedy, William Klugh; Lopez, Gaylord
The misuse and abuse of prescription medications in the United States continues to increase despite interventions by health care professionals, regulatory, and law enforcement agencies. Opioid analgesics are the leading class of prescription drugs that have caused unintentional overdose deaths. Benzodiazepines when taken alone are relatively safe agents in overdose. However, a 5-fold increase in deaths attributed to benzodiazepines occurred from 1999 to 2009. Emergency department visits related to opioid analgesics increased by 111% followed by benzodiazepines 89%. During 2003 to 2009, the 2 prescriptions drugs with the highest increase in death rates were oxycodone 264.6% and alprazolam 233.8%. Therefore, benzodiazepines have a significant impact on prescription drug unintentional overdoses second only to the opioid analgesics. The combination prescribing of benzodiazepines and opioid analgesics commonly takes place. The pharmacokinetic drug interactions between benzodiazepines and opioid analgesics are complex. The pharmacodynamic actions of these agents differ as their combined effects produce significant respiratory depression. Physician and pharmacy shopping by patients occurs, and prescription drug-monitoring programs can provide important information on benzodiazepine and opioid analgesic prescribing patterns and patient usage. Health care professionals need to inform patients and work closely with regulatory agencies and legislatures to stem the increasing fatalities from prescription drug unintentional overdoses.